Kilka uwag o języku i kontekście kulturowym Diariusza podróżnego hetmana Filipa Orlika - Walczak-Mikołajczakowa, Mariola; Mikołajczak , Aleksander Wojciech (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article’s subject of interest is the language of the Travel Diary written by the Cossack hetman Pylyp Orlyk from 1720 to 1732 during a trip from Stockholm to Istanbul. The article refers to the so-called “macaronisation”, i.e. the saturation of the text with Latin and/or Italian words and borrowings from other languages, typical of Polish texts of the Baroque period. A large part is devoted to Turkish words because a significant part of Pylyp Orlyk’s journey went through the lands belonging to the Ottoman Empire in the eighteenth century.